Environmental care attitudes and intention to purchase green products: impact of environmental knowledge, word of mouth, and green marketing - Simanjuntak, Megawati; Nafila, Nidya Luthfi; Yuliati, Lilik Noor; Johan, Irni Rahmayani; Najib, Mukhamad; Sabri, Mohamad Fazli (Multidisciplinary Digital Publishing Institute, 2023)
The intention to purchase green products cannot be separated from environmental consciousness among people. This study analyzes the effect of environmental knowledge, word of mouth (WOM), and green marketing on environmental care attitudes and the intention to purchase green products. A total of 159 valid questionnaires were analyzed with structural equation modeling. The empirical results indicate that environmental knowledge significantly affects environmental care attitudes. In addition, green marketing and environmental concerns significantly and positively affect the intention to purchase green products. Meanwhile, WOM and green marketing do not significantly affect environmental care attitudes. Similarly, environmental knowledge and WOM do not significantly affect the intention to purchase green products. Finally, managerial implications for the government and business were formulated.